THE ROLE OF DILUENTS IN MAINTAINING QUALITY OF BULL SPERM DURING FREEZING - Hastuti Hastuti; Suparman Suparman (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2016)
This study aimed to determine the effect of diluent in maintaining the quality of bull sperm during freezing and physiological processes of bull sperm that occur during freezing. This research was conducted by observing samples of frozen bull sperm that uses diluents, as well as through the assessment of data research with assessment parameters such as macroscopic and microscopic assessment of cattle semen. Data were analyzed using descriptive statistical analysis. The results of this study indicate that the ratings fresh semen is done in two ways, namely macroscopically and microscopically. Grossly obtained volume of average ejaculate of 6 ml with a beige color and acidity levels on average 5.8. The concentration used is 'medium' which is a category of consistency and decent for further processing until the stage of freezing to rethawing. Microscopic assessment that includes an average frequency of motility in the fourth shelter is 70% with 3+ mass motility, percentage of live of fresh semen was obtained in this study was 80%. This value is the percentage of normal life. Based on these results it was concluded that the addition of diluents can reduce the rate of loss of quality (motility and percentage of survival) of bull sperm during the stages of preservation. Andromed diluent best in reducing the rate of decline in the quality of bull sperm during the stages of preservation